Here's the question you clicked on:

55 members online
  • 0 replying
  • 0 viewing

adnanchowdhury

  • 3 years ago

Solve this equation. http://d.pr/i/7RDw (please show your working)

  • This Question is Closed
  1. adnanchowdhury
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    Answer should be: http://d.pr/i/lRJn

  2. anusha.p
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    apply log ...

  3. .Sam.
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    \[e^{9a} + 2e^{3a} - 3e^{a} = 300\] Let \(e^a=y\) \[y^9+2y^3-3y=300\] \[y^9=300+3y-2y^3\] \[ln(y)^9=ln(300+3y-2y^3)\] \[9ln(y)=ln(300+3y-2y^3)\] \[ln(y)=\frac{1}{9}ln(300+3y-2y^3)\] \[ln(e^a)=\frac{1}{9}ln(300+3e^a-2e^{3a})\] \[a=\frac{1}{9}\ln(300+3e^a-2e^{3a})\]

  4. .Sam.
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    This is the proving solution, I don't think you can solve for 'a' all at one side.

  5. Not the answer you are looking for?
    Search for more explanations.

    • Attachments:

Ask your own question

Sign Up
Find more explanations on OpenStudy
Privacy Policy